OBESITY, New life for anti-diabetic drugs - Houtkooper, Riekelt H. (2010)
Anti-diabetic drugs that activate the protein PPARγ had a bright start but soon lost appeal due to undesirable side effects. Subtle modifications may once again make them suitable for treating diabetes.